Composite Fault Feature Extraction of Gearbox based on CPFs - Ye Meitao; Chai Huili (Jixie chuandong)
Due to the improper selection of the method,the leakage diagnosis or misdiagnosis usually occurs when the composite fault features in the gearbox are extracted. As a result of noise,there will be the phenomena of mode aliasing after LMD decomposition. In view of this,a hybrid fault diagnosis method of the gearbox based on CPFs-MOMEDA is proposed. First,the original signal is denoised by LMD,and a series of PFs are obtained. And the false component and the residual component are removed by the correlation coefficient method. Then,the definition of multi-point kurtosis is introduced,and the fault feature period is extracted by calculating the multi-point kurtosis spectrum of each layer of PF,and the PF without periodic impact is eliminated. In order to maintain the integrity of the original signal,PFs with the same period are recombined by the combined product function method. Finally,the recombinant signal is denoised by MOMEDA by setting different period intervals to further extract the fault characteristics. And the method is applied to the feature extraction of gearbox composite faults to verify the feasibility.